TINGKAT KEMATANGAN GONAD KEPITING RAJUNGAN (Portunus pelagicus L.) DI HUTAN MANGROVE TELUK BUO KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Nika, Restia; Sumarmin, Ramadhan; Zeswita, Armein Lusi (Pendidikan Biologi, 2013)
ABSTRACTGonad maturity is as describes the ability of reproduction of aquatic animals including Blue sweemer crab. Rajungan crab Portunus pelagicus L. requires Mangrove area as a place of ( Nursery grounds and Feeding grounds. This study was conducted  to determine the of gonad maturity of Rajungan crab Portunus pelagicus L. in Buo Gulf Mangrove, the Bungus Teluk Kabung, Padang. The research was conducted from May to July 2013 using the descriptive method through observation of gonadal morphology of Rajungan crab Portunus pelagicus L. Data analisis of  Gonad Maturity using the percentage. The result showed that the female Rajungan crab is 33. Gonad Maturity percentage in May - July  Gonad Maturity I : 39.39%, Gonad Maturity II 27.27%, Gonad Maturity III 12.12%, Gonad Maturity IV 12.12%, Gonad Maturity V 9.09%. Observations on physicl-chemical water parameters during three months ware observed that ranged from 28.40 - 30.80C0, salinity from 32.3 to 34.5 ppm, pH 7 - 8, and the depth  65cm - 3m.